Positive and negative elements regulate human interleukin 3 expression. - Mathey-Prevot, B (1990)
The human interleukin 3 (IL-3) promoter is comprised of several cis-acting DNA sequences that modulate T-cell expression of IL-3. These are located within 315 nucleotides upstream of the mRNA start site. Transient expression of reporter genes linked to serially deleted sequences of the IL-3 promoter has allowed mapping of two activator sequences and an interposed repressor sequence. The proximal regulatory region is specific to IL-3 and prerequisite for efficient transcription. Its effect is enhanced by a second, more distal activating sequence consisting of an AP-1 binding site. Between the two activators lies a transcriptional silencer, which is a potent repressor in the absence of the AP-1 site. DNA-nuclear protein binding experiments demonstrate specific complex formation within each of these functional regions. Thus, both positive and negative regulatory elements appear to control expression of the human IL-3 gene in activated T cells.